Study on Electrochromic Effect of Polyaniline Film - Handojo, Lienda; Simangunsong, Junus (UI Scholars Hub, 2003)
Study on Electrochromic Effect of Polyaniline Film. The light transmission factor of an electrochromic film changes reversibly with the application of an electrical voltage. Thereby the transparent film becomes reversibly opaque so that it may be used to control light transmission. In this paper the results of a study on polyaniline film as an electrochromic active material is reported. Polyaniline looks yellow transparent in the reduced state and turns to green-blue at its oxidized state. The electrochromic device considered in this paper was fabricated in planar configuration of ITO glass − polyaniline film − electrolyte − ITO glass which involved 1.0M H2SO4 solution. The measurement of the current density yields voltamograms for several values of the rate of voltage change, while the optical characteristics were measured with ultraviolet-visible spectroscopy. To inspect the light control properties, the intensity of solar radiation propagating through the device was derived. It is found that in its reduced state, the device transmits 70% of the incoming radiation, while in the oxidized state only 11% of the radiation is left. The result of recycling test indicated that film is stable over 5,000 cycles.